THE SOCIALIZATION OF THE LIBRARY AS AN EFFORT TO PROMOTE LIBRARY INFORMATION SERVICES IN SOCIO-COMMUNICATION'S PERSPECTIVE - BAKHTIYAR; DIANITA ROHMATIN SETYANI NUGROHENI ARISAL FIKA BAKTI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
The research intends to describe (1) the rationalization of socialization of the existence of libraries, (2) the socialization is empowered to promote libraries, (3) constraints of library socialization. The research is an objective of comprehensive analysis of details, related to the most important content, namely;rationalization of the socialization of the library's existence intersects with library promotion.The scope of the study is concentrated on the most important topics, namely the importance of library socialization to be empowered to promote library services. The implementation of analyzing requires critical thinking on phenomena, aims to apply conceptualization in historical developments in the past or is happening. Research uses a historical approach, characterized by realistic critical assessmentof the development of a thought. Information sources are primary as the most important element in the primary data base. The method of collecting data, using a research library by reading various kinds of literature on the topic of library socialization and promotion of the useful values ​​of the library, aims to synchronize and harmonize the flow of thought. Data analysis is descriptive qualitative, sourced from an analysis of various kinds of reading materials that are accurate, up to date theoretical, research and not research. The validity of research is realized by requiring efforts to empower content analysis, positive value and constructive analysis of various conceptual meanings in research. Observation is used as a basic element to support theory construction.The research results are; (1)Library socialization to promote library services is the most important marketing strategy, because as the most effective and efficient means of continuous reminding, of the urgency of libraries as centers of learning and information resources, literacy service providers and recreational media. (2) library services can be used optimally, so library socialization is needed to promote library information services. Implementation of promotionnot only using electronic media and print media, but also requires direct action by librarians, (3) library socialization constraints include internal constraints and external constraints.